As transformações na gestão fiscal e a Secretaria da Fazenda e Planejamento do Estado de São Paulo: uma análise sob a perspectiva de Campos de Ação Estratégica - Nero, Maria Patricia de Padua Del (Universidade Federal de São Carlos, 2022)
The present dissertation is dedicated to describing and analyzing the transformations in fiscal management, from 1995 to 2019, which encompassed the Secretariat of Finance and Planning of the State of São Paulo (Sefaz). To understand the changes in this phase, which were driven by movements that occurred at the global and regional levels, in the tax and financial areas, this study also seeks to contextualize the scenario and plot in which they unfolded. From the mid-1990s onwards, at a time when the circulation of goods and services and the mobility of global financial capital were intensifying, marked by an increase in economic, fiscal, financial and structural crises and by greater pressure for the adoption of state reforms of a neoliberal nature, movements were triggered in the fiscal area of several countries that involved: greater exchange of information, sharing of data and experiences; intensification of digitization and training processes; adoption of a set of common norms and rules; and, cooperation and integration between the organizations involved. The idea is that these measures could contribute to the States in combating tax evasion, controlling tax avoidance, adopting measures to adjust public accounts and providing transparent information to managers and investors. In Brazil, this movement incorporates the fiscal management of all federative, federal, state and municipal entities, having implemented in the period programs aimed at fiscal management financed largely with Inter American Development Bank (IDB) resources and which also involved its technical assistance and coordination. ESP participates in these changes through Sefaz, which assumes an active role from the beginning, with participation in several programs (Promocat and Promociaf - Pnafe; Proffis, Profisco I and II). This movement that takes place in a strategic sector of the State, called in this field study fiscal management, involved many relevant actors who were driving forces and/or contributed to its transformation at a global and regional level. Its participants comprise various organizations and social spaces, international, national and subnational. In this dissertation, the transformations in fiscal management are analyzed from the perspective of the Theory of Fields of Strategic Action (TCAE), by Fligstein and McAdam (2012). From this approach, it is assumed that this dynamic involved the interaction between a complex network of fields considered as circumscribed social arenas. It starts with the proposal that any field is embedded in a broader environment, and the source of many of the opportunities and challenges of a given field stem from its relationships with this environment. Movements that occurred during the study period point to the formation of a more structured and integrated international and national tax management, presenting itself as a strategic advantage to be used in the articulation and promotion of agendas for collective discussions of tax and financial policies, in all the levels. This knowledge may also provide Sefaz with the opportunity to improve and expand its relationships in the tax field. The contribution of this study to the academy is also relevant, given the possibility of understanding, through the TCAE, how the processes of change in the State take place, from the perspective of a specific and tactical field of governance, such as the fiscal area. Furthermore, it makes it possible to study an empirical phenomenon from a field perspective, thus seeking to cooperate for collaborative research in fields.
Transformations in fiscal management and the secretariat of treasury and planning of the State of São Paulo: an analysis from the perspective of strategic action fields
Keywords: Teoria dos campos; Campos de ação estratégica; Gestão fiscal; BID; Secretaria de Fazenda do Estado; Secretariat of Finance of the State; Theory of fields; Strategic action fields; Tax management; IDB; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS